A Genetic Network for Systemic RNA Silencing in Plants. Issue 4 (8th February 2018) - Chen, Weiwei; Zhang, Xian; Fan, Yaya; Li, Bin; Ryabov, Eugene; Shi, Nongnong; Zhao, Mei; Yu, Zhiming; Qin, Cheng; Zheng, Qianqian; Zhang, Pengcheng; Wang, Huizhong; et al.
Abstract : A DCL2-dependent DCL genetic pathway is crucial for systemic PTGS in plants. Abstract: Non-cell autonomous RNA silencing can spread from cell to cell and over long distances in animals and plants. However, the genetic requirements and signals involved in plant mobile gene silencing are poorly understood. Here, we identified a DICER-LIKE2 ( DCL2 ) - dependent mechanism for systemic spread of posttranscriptional RNA silencing, also known as posttranscriptional gene silencing (PTGS), in Nicotiana benthamiana . Using a suite of transgenic DCL RNAi lines coupled with a GFP reporter, we demonstrated that N. benthamiana DCL1, DCL2, DCL3, and DCL4 are required to produce microRNAs and 22, 24, and 21nt small interfering RNAs (siRNAs), respectively. All investigated siRNAs produced in local incipient cells were present at low levels in distal tissues. Inhibition of DCL2 expression reduced the spread of gene silencing, while suppression of DCL3 or DCL4 expression enhanced systemic PTGS. In contrast to DCL4 RNAi lines, DCL2 - DCL4 double-RNAi lines developed systemic PTGS similar to that observed in DCL2 RNAi. We further showed that the 21 or 24 nt local siRNAs produced by DCL4 or DCL3 were not involved in long-distance gene silencing. Grafting experiments demonstrated that DCL2 was required in the scion to respond to the signal, but not in the rootstock to produce/send the signal. These results suggest a coordinated DCL genetic pathway in which DCL2 plays an essential role in systemic PTGS in N. benthamiana, while both DCL4 and DCL3 attenuate systemic PTGS. We discuss the potential role of 21, 22, and 24 nt siRNAs in systemic PTGS.